Resúmenes bibliográficos, vol. 29, no. 1 - Clos, Enrique Cristóbal (1953)
Se reseñan las siguientes obras: - Archivo Fitotécnico del Uruguay, entrega 2, volumen 5. - Russell, P. G., Plant inventory no. 153. Plant material introduced by the Division of Plant Exploration and Introduction, Bureau of Plant Industry, Soils, and Agricultural Engineering, Agricultural Research Administration. January 1 to December 31, 1945 (nos. 150.209 to 153.051). 1952. - Russell, P. G., Plant inventory no. 154. Plant material introduced by the Division of Plant Exploration and Introduction, Bureau of Plant Industry. Soils and Agricultural Engineering, Agricultural Research Administration. January 1 to December 31, 1946 (nos. 153.052 to 157.146). 1952. - Parra, A., G. Borgo y F. Valdés, El secado de madera en estufa. 1953. - Macías Arellano, L., Reforestación: teoría y práctica. 1952. - Escalante, M. G., Las mentas cultivadas en la Argentina. 1953. - Revista Agronómica del Noroeste Argentino. Universidad Nacional de Tucumán, Facultad de Agronomía. 1953.